Manufacturing and Management of CAR T-Cell Therapy in “COVID-19’s Time”: Central Versus Point of Care Proposals - Ortiz de Landazuri, Iñaki; Egri, Natalia; Muñoz-Sánchez, Guillermo; Ortiz-Maldonado, Valentín; Bolaño, Victor; Guijarro, Carla; Pascal, Mariona; Juan, Manel (Frontiers in Immunology, 2020)
The SARS-CoV-2 coronavirus (COVID-19) has generated a significant repercussion on the administration of adoptive cell therapies, including chimeric antigen receptor (CAR) T-cells. The closing of borders, the reduction of people transit and the confinement of the population has affected the supply chains of this live-saving medical product. The aim of this mini-review is to focus on how COVID-19 pandemic have affected CAR T-cell therapy, considering the differences between the large-scale centralized productions in the field of the pharmaceutical industry versus the product manufacturing in the academic/hospital environment. We also review different aspects of CAR T-cell therapy and our experience managing them, including patient selection, resource prioritization and some practical aspects to consider for the safe administration. Although hospitals have been forced to change their usual workflows to cope with the saturation of hospitalized patients, we recommend centers to continue offering this potentially curative treatment for patients with relapsed/refractory hematologic malignancies. Thus, appropriate selection criteria, early intervention to attenuate neurotoxicity or cytokine release syndrome with tocilizumab, and prophylactic/preventive strategies to prevent infection are discussed. These considerations may apply to other emerging adoptive cell treatments and the corresponding manufacturing processes.